Measuring Islamic Rural Banks Productivity in Indonesia 2016-2021: Quadrant Analysis, Technological Change, And Covid-19 Pandemic Impact - Herindar, Evania; Uula, Mimma Maripatul; Rusydiana, Aam Slamet (Review on Islamic Accounting, 2021)
The Islamic finance industry in Indonesia is currently a global concern, one of which is financial institutions, so productivity measurement is essential for BPRS in Indonesia. This study tries to analyze the BCC model as a basic model to see the level of productivity in 92 BPRS using the Malmquist productivity index, both in terms of changes in efficiency and changes in technology during the six-year observation period (2016-2021) using the Malmquist Index. There are several findings from this study. First, the overall level of productivity in BPRS shows an increase, and it is known that changes in efficiency and technology affect the increase in productivity of BPRS. Furthermore, in the analysis of each BPRS, it is known that the productivity of the BPRS fluctuates from year to year. Second, the regional study between Java and Non-Java found that BPRS in Java has higher productivity levels than BPRS outside Java, considering that Java is the center of the Indonesian economy and the impact of high technological changes on BPRS in Java. Third, the following finding is related to the productivity of BPRS before and after the Covid-19 pandemic, which showed a decline during the Covid-19 pandemic. Still, the decline was not significant when viewed from the results of statistical tests. Then based on the analysis of the Malmquist Index quadrant, it shows that the BPRS dominates quadrant 2 with the category of high technology and low efficiency, namely back to 25 BPRS, then followed by quadrant 4 with the type of technology and low efficiency, opening 24 BPRS, next is quadrant 3 with a total of 23 BPRS and quadrant one which has the highest category reaches 20 BPRS.